2010
DOI: 10.1111/j.1755-3768.2010.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Phantom pain after eye amputation

Abstract: ABSTRACT.Purpose: To characterize the quality of phantom pain, its intensity and frequency following eye amputation. Possible triggers and relievers of phantom pain are investigated. Methods: The hospital database was searched using surgery codes for patients who received ocular evisceration, enucleation, orbital exenteration or secondary implantation of an orbital implant in the period between 1993 and 2003. A total of 267 patients were identified and invited to participate; of these, 173 agreed to participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
67
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 39 publications
(65 reference statements)
5
67
0
5
Order By: Relevance
“…Fifteen studies reported intravitreal injection of both rtPA and gas [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43]; one of these 15 studies incorporated the results of its own, older article [32,39]. Five studies reported intravitreal rtPA and intravitreal anti-VEGF agents and gas injections [11,12,13,44,45]. In 4 of these 5 studies, next to the rtPA, anti-VEGF agents were administered during surgery; in the fifth study, anti-VEGF was administered during the 4- to 6-week interval after surgery, if clinically indicated [45].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen studies reported intravitreal injection of both rtPA and gas [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43]; one of these 15 studies incorporated the results of its own, older article [32,39]. Five studies reported intravitreal rtPA and intravitreal anti-VEGF agents and gas injections [11,12,13,44,45]. In 4 of these 5 studies, next to the rtPA, anti-VEGF agents were administered during surgery; in the fifth study, anti-VEGF was administered during the 4- to 6-week interval after surgery, if clinically indicated [45].…”
Section: Resultsmentioning
confidence: 99%
“…Vitreous hemorrhage rate ranged from 0–45% in group 1 [25,27,28,29,30,31,32,33,34,35,37,38,40,41,42,43],and 0–43% in group 2 [11,12,13,24,44,45 ](table 3). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations